1967
DOI: 10.1002/rds196724387
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation of Classical Approximations Used in VLF Propagation

Abstract: With some interest, I have read that Pappert, Gossard, ;1nd Roth· muller have developed a comprehensive computer program to obtain numerical results for the propagation . constants of an earth-ionosphere waveguide with an arbitrary electron-density profile. The overall agreement between their approach based on Budden's (1961) work and our method (e.g., Wait and Spies, 1960;Wait, 1960) is quite reassuring. If nothing else, it should lay to rest the contro· versies which have arisen in connection with the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1967
1967
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…In a recent paper (Pappert, Gossard, and Rothmuller, 1967), subsequently referred to as paper I, results of a computer program for VLF propagation in the earth-ionosphere waveguide were presented. The appendix of that paper was devoted to the problem of allowing simultaneously for earth curvature and ionospheric effects in regions where both effects may be comparable.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper (Pappert, Gossard, and Rothmuller, 1967), subsequently referred to as paper I, results of a computer program for VLF propagation in the earth-ionosphere waveguide were presented. The appendix of that paper was devoted to the problem of allowing simultaneously for earth curvature and ionospheric effects in regions where both effects may be comparable.…”
Section: Introductionmentioning
confidence: 99%
“…For further discussion on the VLF propagation theory, the interested reader is referred to Wait [1970]. Additional studies on long‐range VLF propagation and their interaction with the lower (D‐layer) ionosphere layer, directional effects (easterly westerly propagation) as well as the ground conductivity role have been carried out by Papert et al [1967], Pappert and Hitney [1988], Ries [1967], Taylor [1960a, 1960b], Challinor [1967] and Ferguson [1992] accounting both for day and nighttime propagation regimes.…”
Section: Modeling the Lightning‐induced Sferics Wave Propagationmentioning
confidence: 99%
“…Propagation of radio waves in the very low frequency (VLF) regime (10 to 30 kHz) and the lower end of the low frequency (LF) regime (30 to 60 kHz) is modeled using a waveguide defined by the Earth's surface and the ionosphere. This waveguide model has been detailed in a series of documents which describe the initial model and its subsequent development [Gessard et al, 1966;Pappert et al, 1967Pappert et al, , 1970Sheddy et al, 1968a, b;Pappert and Smith, 1971;Sheckey, 1972, 1974;Merritt and Shellman, 1976;Pappert and Ferguson, 1986;Shellman, 1986;Ferguson and Snyder, 1987;Pappert and Hitney, 1988]. Although the model can use profiles of particle density and collision frequency specified as arbitrary functions of height, in practice, exponential profiles of ionospheric electron conductivity (which is essentially the scaled ratio of electron density to collision frequency) are used with positive ions assumed for charge neutrality [Bickel et al, 1970;Merritt, 1977;Ferguson, 1980;Ferguson et al, 1985;Merritt et al, 1981; In the past we have found data collected aboard in-flight aircraft to be most useful for selecting ionospheric profiles.…”
Section: Introductionmentioning
confidence: 99%